2013
DOI: 10.1021/sc4002802
|View full text |Cite
|
Sign up to set email alerts
|

Friedel–Crafts Acylation Using Solar Irradiation

Abstract: In recent decades, scientists have attempted to make more environmentally friendly chemical synthesis procedures. One area of environmental concern is the amount of electricity required to complete an experiment. An effective means for minimizing the amount of electricity needed to drive chemical reactions to completion is proposed through the use of solar parabolic reflectors. The proposed solar reflectors are assembled by covering unused satellite dishes with Mylar tape, giving the satellite dish reflective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The same design for the solar reflector was used as the reflector in our previous publication (11). However, we did make one slight adjustment to the set-up.…”
Section: Development Of the Solar Heat Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…The same design for the solar reflector was used as the reflector in our previous publication (11). However, we did make one slight adjustment to the set-up.…”
Section: Development Of the Solar Heat Sourcementioning
confidence: 99%
“…We provided a detailed investigation on the seasonal and weather limitations of the solar reflector heat source in our previous publication (11). The work in that publication demonstrated that the solar reflector heat source can be used successfully during any time of the year as long as there is enough sun present to produce at least approximately 600 W/m 2 of solar irradiation.…”
Section: Seasonal and Weather Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that solar energy could be used to perform high temperature chemical reaction as the heat source [9][10][11][12]. A solar reflector was designed out of satellite dishes and Mylar ® tape, and a Friedel-Crafts acylation reaction was performed using the solar reflector as the sole thermal heat source.…”
Section: Introductionmentioning
confidence: 99%